A radiographic analysis of the abnormal hallux interphalangeus angle range: Considerations for surgeons performing Akin osteotomies. (9th April 2019) - Nguyen, Jacqueline K; Sullivan, Martin; Alpuerto, Bernardino B; Mueller, Samuel; Sly, Nicole
Purpose: This study is aimed to determine the abnormal radiological hallux interphalangeus angle (HIA) range, which can assist surgeons in determining the required bone resection in an Akin osteotomy of the proximal phalanx of the great toe. Methods: Radiographs of 141 feet were analyzed. The mean HIA and range were calculated. Results: The prevalence of hallux valgus interphalangeus (HVI) deformity was 78% (110/141). The mean HIA was 13.5° ± 4.5° (1.4–24.4). Fifty percent had abnormal HIA values of 10–15°, 40% had values of 15–20°, and 10% had greater than 20°. A large proportion of patients with HVI deformities may need greater than the standard 2–3-mm bone wedge removal during Akin osteotomy. Conclusion: The high prevalence and wide range of HVI deformities should alert surgeons to the possibility that greater than 3-mm bone wedge resections may be required. Level of Evidence: Level IV.